Advances in the Study of the Relationship Between Orthodontics and Periodontitis - Han, Lu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This comprehensive study employed a multifaceted research methodology encompassing a systematic review of existing literature, clinical case analyses, and a series of controlled clinical trials to explore the complex relationship between orthodontic treatments and periodontal health. The study focused on evaluating the biomechanical impacts of orthodontic procedures on the periodontium, including risks such as gum recession and bone loss, particularly in patients with varying periodontal biotypes and pre-existing periodontal conditions. The research methodology involved detailed assessments of periodontal health pre- and post-orthodontic intervention, monitoring changes in gingival and bone structures using advanced imaging techniques, and recording patient-reported outcomes regarding oral health quality. The findings of this study revealed a significant correlation between orthodontic force application and changes in periodontal tissue health, highlighting the necessity of personalized treatment planning that incorporates the patient's periodontal status. Preventive measures, including the use of controlled orthodontic forces, meticulous monitoring of tooth movement, and enhanced oral hygiene practices, were shown to be effective in minimizing periodontal complications. This study contributes significantly to the dental field by providing a deeper understanding of the orthodontic-periodontal relationship and offers practical guidelines for dental professionals in managing orthodontic treatments for patients with periodontal considerations. The study's findings underscore the importance of an interdisciplinary approach in dental care, advocating for closer collaboration between orthodontists and periodontists to optimize treatment outcomes and ensure comprehensive oral health care.